Interplay between sex, age, BMI, health-related quality of life, and coping strategies in amateur and professional athletes - Sapuppo, Walter; Giacconi, Davide; Monda, Antonietta; Messina, Antonietta; Saccenti, Daniele; Mineo, Claudia Maria; Casillo, Maria; Allocca, Salvatore; Michelini, Giovanni; Gregori Grgič, Regina; Monda, Vincenzo; Lamanna, Jacopo; et al. (Frontiers in Physiology, 2025)
Background/ObjectivesThe psychological well-being of athletes has garnered increasing interest due to its strong association with physical performance. While somatic indicators such as Body Mass Index (BMI) are routinely monitored in sports, the role of psychological resources—especially coping strategies—in shaping Health-Related Quality of Life (HRQoL) remains underexplored. This study aimed to investigate the influence of psychological and physical factors on HRQoL among amateur and professional athletes, controlling for sex, age, and BMI.MethodsA cross-sectional design was adopted, involving 537 athletes (326 males, 211 females; mean age = 32.44, SD = 13.64), aged 18–76 years. Participants were recruited via online platforms and sports organizations and completed a battery of self-report questionnaires, including the SF-36 to assess HRQoL and the COPE-NVI-25 to evaluate coping strategies. BMI was calculated from self-reported height and weight. Hierarchical multiple regression analyses were performed to assess the relative contributions of demographic, anthropometric, and psychological variables to HRQoL.ResultsDemographic variables and BMI explained a limited proportion of the variance in HRQoL. In contrast, coping strategies significantly contributed to HRQoL outcomes, accounting for up to 22.5% of the variance in the global SF-36 score. Positive attitude and social support were associated with better physical and mental health, while avoidance strategies showed consistent negative associations across all HRQoL dimensions.ConclusionAdaptive coping strategies, particularly positive attitude and social support, play a pivotal role in enhancing athletes’ HRQoL, surpassing the influence of BMI, sex, and age. These findings support the development of tailored psychological interventions to foster athlete wellbeing across competitive levels.